PLANTING OF RHIZOPORA TYPES IN MANGROVE FORESTS PERCUT SEI TUAN NORTH SUMATERA - Ridahati Rambey; Delvian; Deni Elfiati (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Mangrove forest is a tropical beach vegetation community dominated by several tree species that can grow and develop in tidal and muddy beaches. Some mangrove areas recently have been damaged due to illegal activities carried out by various parties, one of which is the East Coast of Sumatra in the Sub District Percut Sei Tuan, Deli Serdang District, Province of North Sumatra. The purpose of the activities is to focus on replanting mangrove lands that have been damaged by local species. The growned in Tanjung Rejo Village Percut Sei Tuan buds are like Rhizopora stylosa, Rhizopora apiculata and Avicennia marina type. Percentage of growing plants were R. stylosa (92.37%), R. apiculata (90%), mixed propagules of R. stylosa and R. apiculata (90%) and A. marina (56%) respectively. Overall the rehabilitation of mangrove forest is categorized as successful, but only one species of the smallest growing with percentage is A. marina (56%) this is because the location of planting is adjacent to the sea where the plants can not stand the tidal currents.